(untitled) (Research, Society and Development, 2024)
The offer of hypoallergenic and nutritious foods is important for the physical and psychological well-being of consumers allergic to milk. Approximately 8% to 20% of infants and adults experience some condition due to milk consumption, such as lactose intolerance or allergies. The presence of proteins in milk with allergenic potential can cause digestive problems to skin rashes. Milk protein allergics express various reactions when exposed to this food. These manifestations depend on the degree of allergy and the type of protein involved, and are characterized by respiratory to gastrointestinal symptoms. Commonly, the development of this allergy in children occurs within the first year of age, or until the age of five in other cases. In light of this information, there has been the development of A2 milk, also known as A2A2, which comes from cows with the genotype that favors the synthesis of beta-casein A2 in milk. This selected milk reduces the development of discomfort in the bodies of individuals sensitive to beta-casein A1. In this context, milk containing only beta-casein A2 becomes an alternative for better digestion and quality in dairy consumption for those who are not allergic and who feel some discomfort when consuming milk. Therefore, the literature review aims to address the consumption of A2A2 milk, emphasizing the difference between beta-caseins A1 and A2, describing the characteristics of the allergic condition caused by them, and differentiating it from other conditions resulting from dairy consumption, such as lactose intolerance.